Evolution of the concept of invocation as regards protected designations of origin and protected geographical indications in the case law of the Court of Justice of the European Union - Sánchez Jaraba, José Ramón (Przegląd Prawa Rolnego, 2023)
Protected Designations of Origin and Protected Geographical Indications are, at the European Union level, the main forms of protection afforded to high-quality agricultural products linked to a specific geographical origin. Despite the fact that they belong to two different sets of rules, the European Union seeks to establish a most harmonised legal framework that would provide a uniform response in relation to these quality categories. The latest Regulation (EU) No 2117/2021 of the European Parliament and of the Council of 2 December 2021 amends Regulations (EU) 1151/2012 and 1308/2013 in order, inter alia, to approximate the definitions of the “designation of origin” and “geographical indication” contained in these acts. Both texts protect the aforementioned quality categories, alongside other prohibited activities, from any misuse, imitation or invocation to which they could be subject. The concept of reference arose in particular at the interpretative level of the Court of Justice of the European Union between the oldest judgment of March 1999 and this most recent one of September 2021. The aim of this paper is to show the evolution of this concept for a better understanding of its scope and importance.